The effect of cyber attacks on stock performance Bank Syariah Indonesia - Nisa, Zahra Fatikhatun; Cahyono, Yuli Tri (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to assess the stock performance of PT Bank Syariah Indonesia (BSI) prior to and during a cyber crime incident targeting its central server on May 8th, 2023. The stock performance of BSI shares on the capital market is forecast based on abnormal returns and trading volume activities. Quantitative research is being conducted using the event study approach. The research sample includes data for BSI shares registered on the capital market under the issuer's code BRIS. Researchers processed and analyzed the data using the Wilcoxon Signed Rank Test, facilitated by the IBM SPSS 25 software. The research findings indicate that the occurrence of the cyber crime event had no impact on the abnormal returns and trading volume activity of BSI shares. Therefore, there was no significant difference in the performance of the two stock variables, both before and after the incident. The event can be used as evaluation material for BSI to keep update and hardening its cyber security system, as well as to ensure transparency of information with investors. Investors can also get some learning to be calm and actively looking for information about the stock and company conditions related to their shares in order to avoid losses when they are facing with similar events.